Pengaruh Profitabilitas Dan Likuiditas Terhadap Harga Saham Pada Perusahaan BUMN Perbankan Di BEI Pada Periode 2016-2020 (Studi Empiris pada perusahaan BUMN Perbankan yang Terdaftar di BEI pada tahun 2016-2020) - Fahmi Aldian Yuhanata; Muhammad Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to determine the effect of profitability and liquidity on stock prices in state-owned banking companies on the IDX in the 2016-2020 period (Empirical Study on state-owned banking companies listed on the IDX in 2016-2020). This research uses quantitative methods. Determination of the sample in the study using a saturated sampling technique that is all the population is sampled so that the number of samples obtained is 80 samples from 4 companies. The analytical tool used in this study is multiple linear regression analysis. The results of this study indicate that profitability and liquidity on stock prices simultaneously have a significant effect on stock prices in state-owned banking companies on the IDX in the 2016-2020 period. While partially profitability on stock prices has no significant effect on stock prices. And the liquidity variable partially has a positive and significant effect on stock prices in state-owned banking companies on the IDX in the 2016-2020 period. Keywords: Profitability, Liquidity And Stock Price